2018
DOI: 10.1186/s13195-018-0444-1
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between plasma and PET beta-amyloid levels in individuals with subjective cognitive decline: the Fundació ACE Healthy Brain Initiative (FACEHBI)

Abstract: BackgroundPeripheral biomarkers that identify individuals at risk of developing Alzheimer’s disease (AD) or predicting high amyloid beta (Aβ) brain burden would be highly valuable. To facilitate clinical trials of disease-modifying therapies, plasma concentrations of Aβ species are good candidates for peripheral AD biomarkers, but studies to date have generated conflicting results.MethodsThe Fundació ACE Healthy Brain Initiative (FACEHBI) study uses a convenience sample of 200 individuals diagnosed with subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 66 publications
9
46
0
Order By: Relevance
“…These results are consistent with our previous findings showing an inverse association between the Aβ42/40 plasma ratios, particularly TP42/40, and cortical Aβ burden in an AIBL subcohort of cognitively normal controls 3 and other independent cohorts. 10,32 In agreement with this, it has previously been reported that the plasma Aβ42/40 ratio correlated directly with Aβ 42 CSF levels and inversely with Aβ-PET SUVR. [4][5][6][7][8][9] Moreover, our present results support previous community-based studies in healthy people reporting an association between lower plasma Aβ42/40 ratio and greater cognitive decline 12 or increased risk of developing AD dementia at follow-up.…”
Section: Discussionsupporting
confidence: 69%
“…These results are consistent with our previous findings showing an inverse association between the Aβ42/40 plasma ratios, particularly TP42/40, and cortical Aβ burden in an AIBL subcohort of cognitively normal controls 3 and other independent cohorts. 10,32 In agreement with this, it has previously been reported that the plasma Aβ42/40 ratio correlated directly with Aβ 42 CSF levels and inversely with Aβ-PET SUVR. [4][5][6][7][8][9] Moreover, our present results support previous community-based studies in healthy people reporting an association between lower plasma Aβ42/40 ratio and greater cognitive decline 12 or increased risk of developing AD dementia at follow-up.…”
Section: Discussionsupporting
confidence: 69%
“…To our knowledge, we provide the first application of a novel, highthroughput technique for plasma A␤ analysis [43] to a research study that was run independently of the manufacturer. The assay had previously been used in four studies [28,45,47,48] of which one [47] used a subsample of an earlier investigation [45]. In sum, the studies found correlations of plasma A␤ 42/40 with CSF A␤ 42/40 [45], as well as associations of low plasma A␤ with presence of [28,45,47,48] and an increased 3-year accumulation of A␤ burden on PET [28].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, all samples were processed blinded to the diagnostic group or amyloid status. We analyzed two ratios, free plasma Aβ42 to free Aβ40 (Aβ F42:F40) and total plasma Aβ42 to total Aβ40 (Aβ T42:T40), as they had been previously shown to correlate with amyloid positivity [5,13,16,36].…”
Section: Methodsmentioning
confidence: 99%
“…In addition, all samples were processed blinded to the diagnostic group or amyloid status. We analyzed two ratios, free plasma Ab42 to free Ab40 (Ab F42:F40) and total plasma Ab42 to total Ab40 (Ab T42:T40), as they had been previously shown to correlate with amyloid positivity [5,13,16,36]. After a 90-minute uptake period, PET data were acquired for 20 minutes (90-110 minutes) using continuous list mode acquisition on a Siemens mCT.…”
Section: Plasma Ab Assaymentioning
confidence: 99%
See 1 more Smart Citation